2016
DOI: 10.1165/rcmb.2015-0068oc
|View full text |Cite
|
Sign up to set email alerts
|

Nogo-B Receptor Modulates Pulmonary Artery Smooth Muscle Cell Function in Developing Lungs

Abstract: Nogo-B and its receptor (NgBR) are involved in blood vessel growth in developing lungs, but their role in pulmonary artery smooth muscle cell (PASMC) growth is unknown. We hypothesized that NgBR regulates growth of PASMCs by modulating the function of endoplasmic reticulum (ER) and formation of reactive oxygen species (ROS). In utero constriction of the ductus arteriosus created pulmonary hypertension in fetal lambs (hypertensive fetal lamb [HTFL]). PASMCs isolated 8 days after surgery were assessed for the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…Decreased NgBR expression is observed in PAECs and PASMCs of PPHN fetal lambs, contributing to abnormal angiogenesis, mediated through increased levels of ROS ( Figure 6). Its knockdown reproduces PPHN phenotype, and its overexpression reverts the abnormalities in both cell types of PPHN lamb models (145,146).…”
Section: Nogo-b/ngbr Pathwaymentioning
confidence: 99%
See 3 more Smart Citations
“…Decreased NgBR expression is observed in PAECs and PASMCs of PPHN fetal lambs, contributing to abnormal angiogenesis, mediated through increased levels of ROS ( Figure 6). Its knockdown reproduces PPHN phenotype, and its overexpression reverts the abnormalities in both cell types of PPHN lamb models (145,146).…”
Section: Nogo-b/ngbr Pathwaymentioning
confidence: 99%
“…Recently, it has been shown that Nogo-B/NgBR pathway, involved in pulmonary vascular development, is altered in fetal lambs with PPHN ( 145 , 146 ) ( Figure 1 ). Decreased NgBR expression is observed in PAECs and PASMCs of PPHN fetal lambs, contributing to abnormal angiogenesis, mediated through increased levels of ROS ( Figure 6 ).…”
Section: Pathophysiology and Targeted Therapeutic Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Follow-up studies suggest that the cytoplasmic domain of NgBR resembles hydrophobic pockets to bind prenylated Ras and promotes its accumulation and activation at the membrane. Recently, it was reported that the decrease of NgBR expression promoted PASMC proliferation through regulation of reactive oxygen species (ROS) production in an intrauterine pulmonary hypertension (IPH) model [16]. However, the underlying mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%